Acclimation mechanisms elicited by sprayed abscisic acid, solar UV-B and water deficit in leaf tissues of field-grown grapevines - Alonso, Rodrigo Emanuel (2015)
The independent and interactive effects of solar ultraviolet-B radiation (UV-B), moderate water deficit and sprayed abscisic acid (ABA) on leaves gas exchange and biochemical aspects of field-grown grapevines of the cv. Malbec were investigated in a high altitude vineyard (1450 m a.s.l.). Two UV-B treatments (ambient solar UV-B or reduced UV-B), two watering treatments (well watered or moderate water deficit) and two ABA treatments (no ABA and sprayed ABA) were given alone and combined in a factorial design. Gas exchange and photosynthesis were reduced by water deficit and highly impaired in the UV-B and water deficit combined treatment. UV-absorbing compounds were stimulated independently by UVB. The monoterpenes α-pinene, 3-carene and terpinolene, and the sesquiterpene nerolidol were augmented by UV-B, water deficit or sprayed ABA. Levels of the triterpene squalene and the diterpene phytol were significantly higher in the treatment that combined UV-B, water deficit and ABA applications. Environment signals (solar UV-B and moderate water deficit) and sprayed ABA elicited mechanisms of acclimation by augmenting the content of terpenes with antioxidant and antifungal properties, thus enhancing the plant defensive mechanisms towards signals both biotic and abiotic.